Azathioprine in Rheumatoid Arthritis. Issue 5641 (15th February 1969) - Mason, Michael; Currey, H. L. F.; Barnes, Colin G.; Dunne, J. F.; Hazleman, B. L.; Strickland, I. D.
Abstract : The ability of azathioprine to reduce the corticosteroid requirements of patients with severe rheumatoid arthritis was tested under double-blind conditions against placebo. After 12 months a significant mean dose reduction of 36% was achieved without undue side-effects. This form of therapy promises to be an advance in the management of severe rheumatoid arthritis.